Taxonomic relationship of vole agent to Rochalimaea quintana. - Myers, W F (1979)
We investigated the recent claim that the vole agent, a rickettsia-like microorganism isolated from wild voles by Baker in 1946, is actually a strain of Rochalimaea quintana, the etiological agent of trench fever. The two organisms were compared on the basis of percent guanine-plus-cytosine content, genome size, deoxyribonucleic acid-deoxyribonucleic acid hybridization, polypeptide composition, and serological relationships. Although the two organisms do have identical or nearly identical deoxyribonucleic acid base ratios and show some serological cross-reactions, they differ substantially by all of the other criteria employed. They are clearly different, although possibly related, organisms. It remains to be determined whether they can be regarded as two species of the same genus. On the other hand, an Old World strain and a New World strain of R. quintana were indistinguishable from one another by the same criteria.